2013
DOI: 10.1073/pnas.1302500110
|View full text |Cite
|
Sign up to set email alerts
|

Organization of lampreyvariable lymphocyte receptor Clocus and repertoire development

Abstract: Jawless vertebrates are pivotal representatives for studies of the evolution of adaptive immunity due to their unique position in chordate phylogeny. Lamprey and hagfish, the extant jawless vertebrates, have an alternative lymphocyte-based adaptive immune system that is based on somatically diversifying leucine-rich repeat (LRR)-based antigen receptors, termed variable lymphocyte receptors (VLRs). Lamprey T-like and B-like lymphocyte lineages have been shown to express VLRA and VLRB types of anticipatory recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…The germ-line VLR genes are incomplete in that they only contain coding sequences for the leader sequence, incomplete aminoand carboxyl-terminal LRR subunits (LRRNT and LRRCT) and the stalk region (4,7,8). However, each germ-line VLR gene is flanked by hundreds of different LRR-encoding sequences, which can be used as templates to add LRR sequences during the assembly of a mature VLR gene (4,(8)(9)(10)(11). This gene conversionlike process is postulated to involve the activation-induced cytidine deaminase (AID) orthologs, cytidine deaminases 1 and 2 (CDA1 and CDA2) (8,12).…”
mentioning
confidence: 99%
“…The germ-line VLR genes are incomplete in that they only contain coding sequences for the leader sequence, incomplete aminoand carboxyl-terminal LRR subunits (LRRNT and LRRCT) and the stalk region (4,7,8). However, each germ-line VLR gene is flanked by hundreds of different LRR-encoding sequences, which can be used as templates to add LRR sequences during the assembly of a mature VLR gene (4,(8)(9)(10)(11). This gene conversionlike process is postulated to involve the activation-induced cytidine deaminase (AID) orthologs, cytidine deaminases 1 and 2 (CDA1 and CDA2) (8,12).…”
mentioning
confidence: 99%
“…Previous work has identified in lamprey larvae a thymus equivalent (referred to as the thymoid), situated at the tips of the gill filaments; this lymphoepithelial tissue is characterized by the expression of genes such as FOXN1 and DLL4 that are also found in the thymopoietic tissues of jawed vertebrates (18). These findings, together with the observations of a high frequency of incomplete and nonfunctional VLRA (18) and VLRC (6,19) assemblies and the expression of the CDA1 gene (18), indicate that VLRA and VLRC receptor genes are assembled in this tissue.…”
mentioning
confidence: 70%
“…This insert, whose secondary structure also varies, is critical for recognition of protein and carbohydrate antigens (14,15,(22)(23)(24)(25). The average length of the LRRCT insert in VLRCs (2 residues) is much less than in VLRAs (10 residues) or VLRBs (8 residues), and sequence variation in the LRRCT module of VLRCs is substantially lower than in LRRCT of the other two VLR types (19,29). In the VLRC.1MP structure, the LRRCT insert comprises only 2 residues and does not protrude from LRRCT or extend across the concave surface of the VLR.…”
Section: Resultsmentioning
confidence: 99%
“…The three VLR isotypes are differentially expressed by three distinct populations of lymphocytes in lampreys (9,13). The two types of T-like cells of lamprey, VLRA + and VLRC + lymphocytes, are generated in the thymoid, a lymphoepithelial tissue equivalent to the thymus (13)(14)(15); this situation is analogous to the development in the thymus of the two distinct αβ and γδ T-cell lineages in jawed vertebrates. The VLRB + cells appear to be generated in hematopoietic tissues outside of the thymoid (14), much like B cells in jawed vertebrates.…”
mentioning
confidence: 94%
“…The germ-line VLRC gene in lampreys is flanked by five types of donor LRR-encoding cassettes, which contribute to the assembly of mature VLRC genes in a stepwise manner ( Fig. 1 A and B): 3′ LRRNT-5′ LRR1 cassettes, 3′ LRR1-5′ LRRV cassettes, 3′ LRRV-5′ LRRV cassettes, 3′ LRRVt-CP-5′ LRRCT cassettes, and LRRCT cassettes (15). In an assessment of genomic donor cassettes contributing to the assembly of mature VLRA, VLRB, and VLRC genes, we found that four types of the genomic donor cassettes (3′ LRRNT-5′ LRR1, 3′ LRR1-5′ LRRV, 3′ LRRV-5′ LRRV, and 3′ LRRVt-CP-5′ LRRCT) may be shared in the assembly of the VLRA and VLRC genes (Fig.…”
Section: Figs S2-s4)mentioning
confidence: 99%